Pravica do svobode izražanja v času umetnointeligenčnih sistemov - Sancin, Vasilka (Pravni letopis, 2024)
This article examines the impact of the development and use of artificial intelligence on the fundamental right to freedom of expression. Technologies using AI systems are not inert or neutral and often reflect the values and prejudices of their creators and users, which can have an impact on society and democratic processes. Their use brings both benefits and risks for freedom of expression, as algorithms decide which content is accessible to users, which can lead to bias, limit pluralism and create so-called „echo chambers“. In addition, the automatic removal of content using artificial intelligence often leads to excessive restrictions, as algorithms cannot adequately identify context and emotion. States have a duty to ensure that AI systems do not undermine the right to freedom of expression, including the right to information. This paper offers a critical analysis of the existing international regulatory framework and the possibilities for future legal developments, including the adoption of a global international treaty that would comprehensively regulate AI and its human rights impacts. Such an approach could make an important contribution to overcoming fragmentation and creating a level playing field for technological development based on the protection of human rights, while, in view of the rapid pace of development, it would be important to foresee the possibility of adapting to different future situations.
Keywords: artificial intelligence; international human rights law; mednarodna regulacija; mednarodno pravo človekovih pravic; new technologies; nove tehnologije; pravica do informacij; pravica do svobode izražanja; right to information; Svoboda izražanja; the right to freedom of expression; Umetna inteligenca